2009
DOI: 10.1111/j.1540-8159.2009.02370.x
|View full text |Cite
|
Sign up to set email alerts
|

Troponin Levels after Cardiac Electrophysiology Procedures: Review of the Literature

Abstract: Cardiac-specific Troponins (cTn) I and T have become markers of choice for myocardial injury. We reviewed the literature in order to understand the expected postprocedure cTn rise after electrophysiology procedures. A total of 34 studies and 1,608 patients were included. After external monophasic cardioversion, seven of 442 patients (1.6%) had minimal increase in cTnI (0.1-0.9 ng/mL), and only one of 368 (0.3%) had increase in cTnT (0.11 ng/mL). After internal cardioversion, 17 of 105 (16%) had increase in cTn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 90 publications
0
12
0
1
Order By: Relevance
“…While there is data indicating an elevation in serum troponin after transthoracic shocks, most of these studies show only small and clinically insignificant increases [1,18]. In a meta-analysis of studies after external cardioversions only 7 of 442 patients and 1 of 368 patients showed an increase in cardiac Troponin I and T, respectively [19]. Additionally, myoglobin levels and creatine kinase (CK) activity are non-specific markers for muscle injury and an increase in these markers after transthoracic shocks therefore is not reliable proof of myocardial injury and may be also attributed to skeletal muscle injury [2,4,20].…”
Section: Discussionmentioning
confidence: 99%
“…While there is data indicating an elevation in serum troponin after transthoracic shocks, most of these studies show only small and clinically insignificant increases [1,18]. In a meta-analysis of studies after external cardioversions only 7 of 442 patients and 1 of 368 patients showed an increase in cardiac Troponin I and T, respectively [19]. Additionally, myoglobin levels and creatine kinase (CK) activity are non-specific markers for muscle injury and an increase in these markers after transthoracic shocks therefore is not reliable proof of myocardial injury and may be also attributed to skeletal muscle injury [2,4,20].…”
Section: Discussionmentioning
confidence: 99%
“…A lower cTn level is expected after RF of focal area with few RF lesions. RF ablation of more myocardial tissue in the atria, such as in PV isolation, is expected to have much higher cTn levels [10][11][12][20][21][22][23][24][25]. Previous clinical studies reported contrasting data, in the setting of AF ablation, on cardiac biomarkers levels after cryoballoon ablation compared to RF ablation [7,[13][14][15][16][17][18][19]26].…”
Section: Previous Studiesmentioning
confidence: 99%
“…First studies focused on RF lesion and it has been demonstrated that cTnI and cTnT are more sensitive and specific than CK--MB for the diagnosis of myocardial injury after RF ablation [5,6]. It has also been showed that the rise of biomarkers and the extent of myocardial damage after RF catheter ablation depend on the number of RF pulses and site of ablation [12][13][14][15][16]19]. A lower cTn level is expected after RF of focal area with few RF lesions.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An explicit chart review was undertaken to determine if patients had a history of myocardial infarction or cardiac procedure (percutaneous coronary intervention, coronary artery bypass graft, cardiac ablation, or pacemaker or implantable cardioverter-defibrillator insertion) during the previous month; these patients were excluded due to potential spurious troponin elevation. 15,20,21 At both EDs, the approach to potentially ischemic chest pain is set by protocol. Myocardial infarction is defined, in a manner consistent with the universal definition of myocardial infarction, 22 as a troponin elevation greater than the 99th percentile of the upper reference limit with a greater than 20% change between serial measurements, or troponin elevation with electrocardiographic (ECG) changes in keeping with myocardial infarction.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%